Environmental governance : a report on the next generation of environmental policy - Kettl, Donald F. (Brookings Institution Press, 2002)
Environmental policy has been the focus of reform efforts for more than a generation. Now policymakers face a new and challenging set of issues: how to develop strategies for attacking new environmental problems, how to develop better strategies for solving the old ones, and how to do both in ways that are more efficient, less taxing, and engender less political opposition. On one level, environmental performance is the problem. On a broader level, the question is how reshaped intergovernmental partnerships will affect how America is governed. This book charts the politics of the next generation of environmental policy: how citizens will sort competing goals and responsibilities, how conflict and collaboration will shape the policy options, and how the nation-s political institutions will respond. These issues raise tough political problems that will define which options are viable and how different options will reshape politics. The contributors outline a path to fresh perspectives on the critical problems that must be addressed. Contributors: Christopher H. Foreman Jr. (University of Maryland, Brookings Institution), Donald F. Kettl (University of Wisconsin-Madison, Brookings Institution), Shelley H. Metzenbaum (University of Maryland), Barry G. Rabe (University of Michigan), Graham K. Wilson (University of Wisconsin-Madison) About the Editor Donald F. Kettl is professor of public affairs and political science at the University of Wisconsin-Madison, Robert M. La Follette School of Public Affairs. He is also a nonresident senior fellow at the Brookings Institution. His recent books include The Global Public Management Revolution: A Report on the Transformation of Governance (Brookings, 2000) and The Transformation of Governance: Public Administration for the 21st Century.
Keywords: Environmental policy -- United States.; Environnement -- Politique gouvernementale -- États-Unis.; SCIENCE -- Environmental Science (see also Chemistry -- Environmental); POLITICAL SCIENCE -- Public Policy -- Environmental Policy.; Environmental policy; United States